Evaluation of academic satisfaction and quality in the Covid-19 pandemic: a post-Covid-19 study among the students of Medical Sciences - Salehi-Fard, Mehrdad; Ghanbarian, Marjan; Roudbari, Aliakbar; Atefi, Masoumeh (Shahroud Journal of Medical Sciences, 2025)
Purpose - One of the most important events that happened during the Covid-19 pandemic was the development of the virtual education system, which had effects on the quality of education and the level of student satisfaction with education from various aspects. This study was conducted to check the quality of virtual education and the level of satisfaction of students of different fields in Shahroud University of Medical Sciences. Design/methodology/approach- In this study, standard questionnaires, whose validity and reliability were checked, were completed by students of different fields and academic semesters, and the results were analyzed with the help of SPSS v21 software. Findings- The results of this study showed that the level of education quality and the level of students' satisfaction with virtual education in most of the majors were medium and high. Originality/value- The experience of successful teaching-learning styles can be introduced, specified and evaluated, and it can initiate the cycle of reforming and improving the education process even in critical conditions such as the Covid-19 pandemic.